Clinical and genetic characteristics of concomitant Mucopolysaccharidosis type IVA and neurogenic bladder in children: two case reports and literature review - Zhuhui Ge; Jianhua Mao; Huijun Shen; Yu Xu; Haidong Fu; Weiwei Zhang; Dongyan Li (BMC, 2021)
Abstract Background Mucopolysaccharidosis IVA (MPS IVA; Morquio A syndrome) is a rare autosomal recessive lysosomal storage disorder. Up to now, reports on the clinical characteristics of MPS IVA mainly focused on patients with progressive bone dysplasia and multiple organ damage, while the effects of this disorder on neurogenic bladder have not been reported. Therefore, the aim of the present study is to report two cases of nocturnal enuresis finally diagnosed as neurogenic bladder in MPS IVA. Case presentation Both children were characterized by the presence of pectus carinatum, kyphoscoliosis, nocturnal enuresis, urinary incontinence, normal intelligence, and loss of strength in the legs, diagnosed as neurogenic bladder in association with MPS IVA through the analysis of the clinical characteristics, enzyme activity and genetic testing. In addition, the terminator codon mutation c.1567T > G (p.X523E) and a novel missense mutation c.575A > G (p.E192G) were found in the coding region of the GALNS gene of the 1st patient, while the missense mutation c.488C > A (p.P163H) was found in the coding region of the GALNS gene of the 2nd patient. Conclusions Neurogenic bladder may occur in patients with MPS IVA after spinal cord injury. It is necessary to screen for the diagnosis of MPS IVA in patients with atypical enuresis and skeletal abnormalities through the analysis of the clinical characteristics, enzyme activity and genetic testing.